Dhikr Therapy as an Approach to Handling Auditory Hallucinations in Schizophrenia Patients at Dr. RM. Soedjarwadi Mental Hospital - Novitasari, Eka; Diktina, Amalia Arifatul; Reknoningsih, Wahyu (Al-Hijrah Indonesia, 2025)
Background: The incidence of schizophrenia in Indonesia reaches 400,000 people or 1.7 per 1,000 population, where Central Java has 8.7% of the population experiencing schizophrenia. 70% of patients diagnosed with schizophrenia experience auditory hallucinations. Auditory hallucinations are stimulus disturbances where the patient hears voices that are not real. Objective: To determine the results of applying dhikr therapy on the ability to control auditory hallucinations in mental disorders patients. Methods: This type of research is a case study that uses descriptive methods with pre-test and post-test observation sheets. Results: The change score in the ability to control hallucinations in 2 respondents before dhikr therapy was carried out was at stage II (moderate) where respondent 1 got a score of 27 and respondent 2 with a score of 31. After being given dhikr therapy for three days, the respondent experienced a change in score to stage I (mild) hallucinations where respondent 1 got a score of 16 and respondent 2 with a score of 21. Conclusion: There are differences in changes in the ability to control hallucinations before and after dhikr therapy in patients with auditory hallucinations.